The Effect of Profitability and Leverage on Sustainability Report Disclosure - Deru Darbeni; Zaharuddin Zaharuddin; Ratna Tri Hari Safariningsih (Annals of Justice and Humanity, 2026)
Purpose: This study examines the effect of capital structure and tax avoidance on the value of manufacturing firms listed on the Indonesia Stock Exchange during 2020–2024, aiming to understand how these factors influence firm value, which reflects performance and investor trust. Research Methodology: The research utilizes secondary data from financial reports of 69 firms, selected through proportionate stratified random sampling from a population of 200 companies. Descriptive statistics and multiple regression analysis, using EViews 12, were applied to test the relationship between capital structure, tax avoidance, and firm value. Results: The findings indicate that capital structure and tax avoidance have a negative but statistically insignificant effect on firm value, suggesting they do not significantly influence changes in firm value during the study period. Conclusions: This study concludes that both capital structure and tax avoidance have a negative and insignificant effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The findings suggest that firm value is more influenced by other factors, such as profitability, company growth, corporate governance, and macroeconomic conditions, rather than capital structure and tax avoidance. Limitations: The research contributes to the understanding of the factors affecting firm value in emerging markets, highlighting that capital structure and tax avoidance alone may not be sufficient to explain firm value changes. Contributions: Future studies should consider other variables such as market conditions or corporate governance to provide a more comprehensive understanding of firm valuation.